2018
DOI: 10.1080/19932820.2018.1479599
|View full text |Cite
|
Sign up to set email alerts
|

Predictive study of academic stress with the irritable bowel syndrome in medicine students at a public university in Mexico

Abstract: Background: Irritable bowel syndrome (IBS) is a functional gastrointestinal disorder associated with stress, which may appear by an educational context, given that students are exposed to demands in the academic environment during their education process that may lead to developing diseases. This study reports on the relationship between the IBS and academic stress and compares results of men and women.Methods: A random survey was made of 561 medicine students at a public university in Mexico. The ROMA III cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
1
6
0
7
Order By: Relevance
“…9 In relation to sex, our results contrast with previous studies that mention that females express higher stress and a high emotional reactivity when taking an exam or doing a class presentation, among other academic activities, when compared to males. 1,2 Nevertheless, the results of the present study are similar to those reported by Maestripieri, Baran, Sapienza et al 6 who found that males exhibit higher cortisol concentrations than females before and after taking a computerized test. The authors suggest that the differences in the hormonal response to psychosocial stress largely depends on the subjectivity with which the stressful stimuli are interpreted as a result of variations in context, the participant's personality, and the interindividual variability that is accentuated when the sample size is small.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…9 In relation to sex, our results contrast with previous studies that mention that females express higher stress and a high emotional reactivity when taking an exam or doing a class presentation, among other academic activities, when compared to males. 1,2 Nevertheless, the results of the present study are similar to those reported by Maestripieri, Baran, Sapienza et al 6 who found that males exhibit higher cortisol concentrations than females before and after taking a computerized test. The authors suggest that the differences in the hormonal response to psychosocial stress largely depends on the subjectivity with which the stressful stimuli are interpreted as a result of variations in context, the participant's personality, and the interindividual variability that is accentuated when the sample size is small.…”
Section: Discussionsupporting
confidence: 92%
“…This academic stress can be a natural survival response in the academic environment, which involves different potential stressors, such as exams, class presentations, class participation, tutoring sessions, academic overload, classroom overcrowding, lack of time to complete the work, mandatory work, homework, group work, and competitiveness among classmates. 2 In relation to an educational context, the classroom is an environment where children spend a great amount of time while growing up. From kindergarten until high school graduation, individuals undergo experiences that can be predictors of well-being and success in school.…”
Section: Introductionmentioning
confidence: 99%
“…Irritable bowel syndrome (IBS) is a functional gastrointestinal disorder associated with stress, which may emerge by an educational circumstance, given that students are exposed to requirements in the academic atmosphere during their education progression that may lead to extending diseases [22]. University students are subject to stress due to academic pressure, empowerment and changeover from adolescence to adulthood stage.…”
Section: Discussionmentioning
confidence: 99%
“…Demikian pula dampak yang ditimbulkan kecemasan dapat merugikan individu seperti: kesehatan, kehidupan sehari-hari, kesejahteraan, mengganggu proses kognitif, (misalnya: perhatian; Robinson, Vytal, Cornwell, & Grillon, 2013). Penelitian terbaru menunjukkan hubungan yang signifikan antara tingkat stres akademik yang tinggi, stres mempengaruhi psiko-fisiologis seperti masalah konsentrasi, hambatan mental, kelelahan kronis, mengantuk, dan depresi (Pozos-Radillo, Preciado-Serrano, L., Plascencia-Campos, Morales-Fernández, & 53│ Pengaruh Relaxation Music Therapy (RMT) Pada Kecemasan Akademik Valdez-López, 2018). Dengan demikian, mahasiswa yang mengalami stres dan cemas tinggi sebelum ujian, tidak akan mampu menunjukkan pengetahuan mereka (Prato & Yucha, 2013), sehingga kinerja akademik mereka dapat terganggu (Dendle et al, 2018).…”
Section: Pendahuluanunclassified